Effect of dentures on pharyngeal swallowing function in patients with dysphagia. Issue 10 (5th August 2021) - Takagi, Daisuke; Ohno, Tomohisa; Moriwaki, Motoki; Katagiri, Norimasa; Umeda, Yoshiko; Tohara, Haruka; Nomoto, Akiko; Fujishima, Ichiro
Abstract : Aim: Dentures play an important role in improving masticatory and oropharyngeal swallowing functions in some edentulous patients without dysphagia. However, few studies have been conducted on patients with dysphagia. This study investigated the effect of dentures on pharyngeal swallowing function in patients with dysphagia. Methods: Older inpatients with dysphagia who used well‐fitting dentures were included in the study. Videofluoroscopic swallowing study findings with and without dentures were compared. Pharyngeal residue and area as spatial, the distance between the maxilla and mandible, hyoid bone/laryngeal displacement, and upper esophageal sphincter opening as kinematics, oral/pharyngeal transit time as temporal measurements, and patient‐reported symptoms were evaluated. The primary outcome was the pharyngeal residue measured using the normalized residue ratio scale. Comparisons were made using the paired t ‐test, Wilcoxon signed‐rank test and Fisher's exact test. Results: The mean age of the 27 participants was 86.1 ± 6.8 years. The vallecular residue was more in those without dentures (with dentures: 0.01 [0–0.02], without dentures: 0.03 [0–0.08]; P  = 0.003). The pyriform sinus residue showed no significant difference. Denture removal significantly increased the pharyngeal area. The distance between the maxilla and mandible decreased in the absence of dentures, and other kinematic measurements showed no significant differences. Oral/pharyngeal transit time was prolonged without dentures. Conclusions: Morphological changes caused by the removal of dentures led to pharyngeal expansion, which may result in increased vallecular residue. A treatment plan that considers the effect of dentures on pharyngeal swallowing function may provide rehabilitation that is more effective. Geriatr Gerontol Int 2021; 21: 907–912 .